2019
DOI: 10.21037/jtd.2019.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C alone does not improve treatment outcomes in mechanically ventilated patients with severe sepsis or septic shock: a retrospective cohort study

Abstract: Background: Vitamin C has shown several beneficial effects on sepsis in preclinical studies. However, clinical data supporting these reports are scarce. This study aimed to evaluate whether adjunctive intravenous vitamin C therapy could reduce hospital mortality in patients with severe sepsis or septic shock requiring mechanical ventilation. Methods: For this retrospective cohort study, consecutive medical ICU patients with severe sepsis or septic shock requiring mechanical ventilation were included. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 36 publications
0
32
2
1
Order By: Relevance
“…While many previous studies [ 11 , 44 , 45 ] have confirmed that the body weight was not associated with the prognosis of patients with COVID-19. In addition, the effect of high-dose vitamin C on anti-oxidation and reducing inflammatory reaction did not show significant correlation with body weight based on recent studies [ 30 , 46 ]. Although we did not record the body weight of patients in baseline, the body weight might not affect the results of our study.…”
Section: Discussionmentioning
confidence: 93%
“…While many previous studies [ 11 , 44 , 45 ] have confirmed that the body weight was not associated with the prognosis of patients with COVID-19. In addition, the effect of high-dose vitamin C on anti-oxidation and reducing inflammatory reaction did not show significant correlation with body weight based on recent studies [ 30 , 46 ]. Although we did not record the body weight of patients in baseline, the body weight might not affect the results of our study.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, six studies reported no adverse events related to the intervention [ 9 11 , 19 , 20 , 24 ], while three studies documented more frequent adverse events in patients treated with intravenous vitamin C (hypernatremia n = 24, hospital-acquired infections n = 14, hyperglycemia n = 13, gastrointestinal bleeding n = 3, and fluid overload n = 1) [ 14 , 21 , 25 ]. The remaining eight studies did not specifically address this issue [ 12 , 13 , 15 18 , 22 , 23 ]. With regard to the large population included in this analysis, only little adverse events were reported when considering the extremely high doses of intravenous vitamin C that were used across the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis showed that vitamin C as an adjuvant treatment shortened the duration of mechanical ventilation and ICU stay in non-surgical critically ill patients [ 83 , 84 ]. Although an individual study showed that treatment of septic patients requiring mechanical ventilation with IV vitamin C (6 g/day) did not improve mortality rate [ 85 ], a meta-analysis which enrolled 1210 patients from different clinical trials showed that treatment of critically ill patients with a dose ranging between 3 and 10 g/day of IV vitamin C decreased mortality rate [ 86 ]. In conclusion, all the above observations support the idea of using high dose of IV vitamin C as a part of the supportive management of severe COVID-19.…”
Section: The Role Of Vitamin C In Management Of Ards Sepsis Septicmentioning
confidence: 99%